Notoraja martinezi sp. nov., a new species of deepwater skate and the first record of the genus Notoraja Ishiyama, 1958 (Rajiformes: Arhynchobatidae) from the eastern Pacific Ocean - Concha, Francisco J.; Ebert, David A.; Long, Douglas J. (Zootaxa, 2016)
A new arhynchobatid skate, Notoraja martinezi, sp. nov., is described from four specimens collected from the eastern Central Pacific from Costa Rica to Ecuador and between depths of 1256–1472 m. The new species is placed in the genus Notoraja based on the long and flexible rostrum and its proportionally long tail with respect to total length. This species is distinct from its congeners in the Western Pacific by the straight margins of its rostrum, long anterior lobes of pelvic fins, and its abundant and very well developed caudal thorns.